2017
DOI: 10.4097/kjae.2017.70.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Surgical excision of the breast giant fibroadenoma under regional anesthesia by Pecs II and internal intercostal plane block: a case report and brief technical description: a case report

Abstract: A 22-years-old female patient at 171 cm and 67 kg visited the Department of Breast Surgery of the hospital with a mass accompanied with pain on the left side breast as chief complaints. Since physical examination revealed a suspected huge mass, breast surgeon decided to perform surgical excision and requested anesthesia to our department. Surgery of breast tumor is often under local anesthesia. However, in case of big size tumor, surgery is usually performed under general anesthesia. The patient feared general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
0
8
1
Order By: Relevance
“…Therefore, they cannot block anterior cutaneous branches of the second to sixth TICNs and branches of the supraclavicular nerves. Although several recent studies have also mentioned these limitations of the PECS II block [ 15 , 19 , 20 ], those studies, in contrast to ours, did not demonstrate these limitations.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, they cannot block anterior cutaneous branches of the second to sixth TICNs and branches of the supraclavicular nerves. Although several recent studies have also mentioned these limitations of the PECS II block [ 15 , 19 , 20 ], those studies, in contrast to ours, did not demonstrate these limitations.…”
Section: Discussioncontrasting
confidence: 99%
“…Table 2 summarises the articles included, technique of fascial plane block used and the main outcome related to it. [ 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 ]…”
Section: Resultsmentioning
confidence: 99%
“…Majority of the authors advocate giving a combination of blocks to cover analgesia over whole of the chest wall, axilla and shoulder. [ 14 15 16 17 18 19 20 21 22 23 24 ] The majority of evidence in the application of interfascial plane blocks for breast surgeries exists in the form of case reports or case series. In the reported case reports, these blocks were used with general anaesthesia and were useful in reducing intra- and post-operative analgesic requirements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, they reported bilateral Pecs II and TTP blocks without general anesthesia for bilateral breast resection in a patient with severe obstructive pulmonary disease [12]. Kim et al have reported Pecs II block and internal intercostal plane block without general anesthesia for a huge breast fibroadenoma resection in a patient with fear for general anesthesia [13]. Hong et al have reported modified Pecs II block (below the serratus muscle as the second injection) and pectointercostal fascial block without general anesthesia for partial resection of recurrent breast cancer in a parturient [14].…”
Section: Discussionmentioning
confidence: 99%